Validity and Reliability of Persian Version of HIV/AIDS Related Stigma Scale for People Living With HIV/AIDS in Iran - Davoud Pourmarzi; Ashraf Khoramirad; Hoda Ahmari Tehran; Zahra Abedini (Tehran University of Medical Sciences, 2016)
Objective: To assess the perceived HIV/AIDS related stigma a comprehensive and well developed stigma instrument is necessary. This study aimed to assess validity and reliability of the Persian version of HIV/AIDS related stigma scale which was developed by Kang et al for people living with HIV/AIDS in Iran. Materials and methods: Thescale was forward translatedby two bilingual academic members then both translations were discussed by expert team. Back-translation was done by two other bilingual translators then we carried out discussion with both of them. To evaluate understandability the scale was administered to 10 Persons Living with HIV/AIDS (PLWHA). Final Persian version was administered to 80 PLWHA in Qom, Iran in 2014. Test-retest reliability was assessed in a sample of 20 PLWHA after a week by intra-class correlation coefficient (ICC). Results: Cronbach's alpha coefficient for overall scale was 0.85. Also Cronbach's alpha coefficients for the five subscales were as follows: social rejection (9 items, α = 0.84), negative self-worth (4 items, α = 0.70), perceived interpersonal insecurity (2 items, α = 0.57), financial insecurity (3 items, α = 0.70), discretionary disclosure (2 items, α = 0.83). Test-retest reliability was also approved with ICC = 0.78. Correlation between items and their hypothesized subscale is greater than 0.5. Correlation between an item and its own subscale was significantly higher than its correlation with other subscales. Conclusion: This study demonstrate that the Persian version of HIV/AIDS related stigma scale is valid and reliable to assess HIV/AIDS related stigma perceived by people living whit HIV/AIDS in Iran.